Chlormethine Gel for Treatment of Patients with Mycosis Fungoides: Best Practices and Guidance to Clinicians - Larisa Geskin; Christiane Querfeld; Emmilia Hodak; Neda Nikbakht; Evangelia Papadavid; Marco Ardigò; Ulrike Wehkamp; Martine Bagot (Dermatology and Therapy)
Abstract Background Mycosis fungoides (MF) is the most common form of cutaneous T cell lymphoma. While multiple guidelines provide treatment recommendations, there are currently no clear treatment algorithms for MF. Chlormethine gel is recommended by major treatment guidelines as a first-line option for stage IA–IIA disease, and, on the basis of these guidelines, used in combination with other therapies in patients with advanced-stage MF in clinical practice. Objectives To provide guidance regarding the use of chlormethine gel for patients with all stages of MF, based on clinical expertise. Methods Opinions on best practices regarding the use of chlormethine gel were collected through discussions that involved eight clinicians with extensive experience in treating patients with MF. Results Chlormethine gel can be used as monotherapy in first- or second-line treatment of early-stage MF. In first-line, chlormethine gel monotherapy is prescribed for stage IA MF, and is particularly convenient for patients unable/unwilling to travel for hospital-based phototherapy, patients with thick plaques or palmoplantar involvement, when ultraviolet treatment is contraindicated, and for sanctuary sites. Chlormethine gel is also an appropriate first-line monotherapy for patients with stage IB or IIA MF; it may be used as part of combination regimens in these patients as well. For patients with late-stage MF, skin-directed treatments such as chlormethine gel should be combined with systemic therapies. Conclusions Chlormethine gel is a safe and effective treatment option that can be used in all stages of MF, either as monotherapy or in combination, depending on disease stage and patient characteristics and needs.